Surgical Removal of Embolized PDA Device from Descending Thoracic Aorta A Case Report (Cardiovascular Journal, 2016)
Closure of patent ductus arteriosus (PDA) with device or coil is presently the first line of therapy.but it has got different acute and late complications. A 3 years old male child presented with history of percutaneous closure of the PDA Amplatzer device 18 months back. Now he presented with dislodgement of the device to descending thoracic aorta and reappearance of a large PDA. The child underwent surgical closure of PDA and removal of the device from descending thoracic aorta. We are presenting this case as one of the uncommon late complications of device closure of PDA.Cardiovasc. j. 2016; 8(2): 158-160